1989
DOI: 10.1111/j.1524-4725.1989.tb03164.x
|View full text |Cite
|
Sign up to set email alerts
|

The Accessory Tragus—No Ordinary Skin Tag

Abstract: An accessory tragus can easily be treated by surgical excision. The results are quite satisfactory if care is taken to remove any protuberant portion of underlying cartilage. This lesion is rarely associated with other developmental defects of the first branchial arch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
35
0
2

Year Published

1992
1992
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 9 publications
0
35
0
2
Order By: Relevance
“…It may be solitary or multiple, unilateral or bilateral, pedunculated or sessile, and soft or firm. The size of the papule is usually 3 to 5 mm, and it might be covered with vellus hair 1,2 . There are a few reports of familial AT and cases that result from maldevelopment of the first and second branchial arch 3 .…”
Section: Discussionmentioning
confidence: 99%
“…It may be solitary or multiple, unilateral or bilateral, pedunculated or sessile, and soft or firm. The size of the papule is usually 3 to 5 mm, and it might be covered with vellus hair 1,2 . There are a few reports of familial AT and cases that result from maldevelopment of the first and second branchial arch 3 .…”
Section: Discussionmentioning
confidence: 99%
“…1 Preauricular tags, protuberant fleshy papules located anterior to the tragus or just anterior to the crus of the helix, are commonly found in the neonatal period and are considered to be of minor clinical importance. 2 However, several studies have demonstrated that preauricular tags and pits may be associated with a higher incidence of conductive and/or sensorineural hearing impairment 3,4 and urinary tract abnormalities. 3,5,6 The cause of such associations, whether hereditary or not, has not been determined.…”
mentioning
confidence: 99%
“…The pathophysiological basis of the accessory tragi relates directly to the embryological development of the external ear. The tragus derives from the first branchial arch, while the remaining components of the external ear all are derived from the second branchial arch14 The pathological findings of AT are characterised by a connective tissue structure with abundant hairs often containing a central cartilaginous nucleus 10…”
Section: Discussionmentioning
confidence: 99%